Extraskeletal Para-articular Osteochondroma of the Ankle Joint in a Child: A Case Report. Issue 2 (2020) - Kawakami, Yohei; Hara, Hitomi; Kawamoto, Teruya; Niikura, Takahiro; Kuroda, Ryosuke; Akisue, Toshihiro
Abstract : Case: We present a rare case of extraskeletal para-articular osteochondroma (ESPAOC) in the ankle of a 9-year-old boy, which was causing pain and limiting the range of motion of the ankle joint. The lesion might have also contributed to the deformity of the medial aspect of the talus. Total resection resolved all of the symptoms, with no recurrence at 1-year postoperatively. Conclusion: Operative excision should be considered when ESPAOC directly restricts ankle motion because it can lead to chronic pain and joint degeneration if left untreated.